Psychometric Evaluation of the Nursing Burnout Scale Short : Form: Persian Version - Vakili, MohammadAli (International Journal of Psychosocial Rehabilitation, 2020)
Burnout is a syndrome of emotional, psychological and physical exhaustion, which is defined by the development of negative attitudes toward job. Although nurses are constatly exposed to various degrees of psychological and physical stress related to their workplace, assessment of this issue requires development of a dedicated tool which is concordantwith the culture of each community. The aim of this study was to evaluate psychometric properties of the Nursing Burnout Scale (NBS-short form) in an Iranian population.This study was done on 637 nurses working in 16 hospitals who were selected via stratified probability sampling. The original version of the scale included 65 items in five domains, which was translated to English using the foward- backward strategy. Face validity, content validity and construct validityincluding exploratory factor analysis (EFA) and confirmatory factor analysis (CFA)of the scale were evaluated. Moreover, reliability of the scale was assessed by calculating Cronbach’s alpha.Data were analyzed by SPSS- 16 and AMOS-22.In the EFA process, considering factor loading of ≥0.3 and Eigen value of >1, coping domain was elminited from the factor model structure. After the CFA and goodness-of-fit measurement, the Persian version of NBS was approved with 47 items in four domains. The reliability of the scale was satisfactory with Cronbach’s alpha coefficient of 0.93.The Persian version of NBS is a valid and reliable questionnaire for measuring job burnout. The scale can accurately predict actual problems related to nursing burnout in Iran. The reports produced by this scale can be utilized by the health system for strategic planning and development of preventive and supportive policies.